Kepemimpinan Kepala Madrasah dalam Mengembangkan Inovasi Manajemen Pendidikan Islam di Mi Nurul Anwar Tenggarang Bondowoso - Solehuddin, Sollah; Yunus, Moch (LP3M UNZAH GENGGONG, 2022)
Abstract In the current era of globalization, education is a non-negotiable personal and social obligation. Because basically education is a social process that aims to develop the potential of human life in order to face the demands of the times in the future, along with the developments and changes of the times which are increasingly shifting. Educational management is a science that studies how to organize resources to achieve set goals productively and how to create a good atmosphere for humans who participate in achieving agreed goals. In relation to the development of education, the head of the madrasah has a very important role and task. This is because the head of the madrasa as a leader is one of the factors that encourage the progress of the world of education. This means that madrasa heads are required to have the ability to carry out educational innovations that are no longer relevant to the current situation in order to achieve the development of the nation and state. Meanwhile, the things that must be considered by the madrasah head in carrying out his duties should be that the principal is truly capable and masters both theoretically and practically, in providing guidance to all his subordinates he should be accompanied by real examples so that it can further motivate motivation, innovation should be in MI Nurul Anwar Tenggarang Bondowoso was planned far in advance. whereas for teachers if there are problems in the teaching and learning process they should look for solutions with other teaching staff, they should be able to further enhance their abilities in order to prepare themselves to face the possibilities that will occur. education should seek clarity and direction of the objectives of these programs. Keywords: Madrasah Principal Leadership, Islamic Education Management Innovation